Reconsidering the Drill Method in Music Education: Pedagogical Perspectives and Learning Outcomes - Piter Sembiring; Yudi Sukmayadi; Sandie Gunara (Cantata Deo: Jurnal Musik dan Seni, 2026)
The drill method has long been employed in music education, yet its pedagogical relevance remains debated due to its association with mechanical repetition and limited musical meaning. This study aims to re-examine the role of the drill method in music learning by synthesising pedagogical perspectives, instructional practices, and reported learning outcomes within existing scholarly literature. A qualitative literature review design was employed, involving systematic database searching, study selection based on predefined inclusion criteria, and thematic analysis of selected studies. Data were analysed using a structured analytical framework through coding, categorisation, and cross-study comparison to identify recurring pedagogical patterns and reported learning outcomes. The reviewed studies indicate that drill-based practice consistently supports technical stability, musical accuracy, notation literacy, and performance consistency across diverse educational contexts. However, its effectiveness is strongly dependent on instructional design and pedagogical integration. Drill contributes to meaningful musical development when aligned with clear objectives, guided feedback, and interpretative engagement, but becomes limited when applied as isolated repetition. This study positions drill as a foundational pedagogical strategy that supports progressive musical learning rather than as a purely mechanical method.